DAUR NAIK LIMBAH TEKSTIL UNTUK PRODUK FESYEN READY TO WEAR DELUXE DENGAN TEKNIK QUILTING - Fajar, Elina Almara; Falah, Asep Miftahul; Atik, Saftiyaningsih Ken (Jurusan Seni Rupa ISBI Bandung, 2024)
This research aims to explore the potential of textile waste recycling in the manufacture of deluxe ready-to-wear fashion products by applying quilting techniques. Against the background of the textile industry that generates huge waste and significant environmental impact, this research tries to provide a sustainable solution by utilizing textile waste as the main material. The Design Thinking method is used in five stages, namely Empathize to understand user needs and problems faced, Define to determine the problems to be solved, Ideate to generate creative ideas, Prototype to create initial products, and Test to test products with potential users. It is hoped that the results of this research can contribute to the development of environmentally friendly and innovative fashion products.